Tandem Functionalization‐Carboxylation Reactions of π‐Systems with CO2. Issue 11 (22nd September 2021) - Bertuzzi, Giulio; Cerveri, Alessandro; Lombardi, Lorenzo; Bandini, Marco
Abstract: The tandem catalytic functionalization/carboxylation of double as well as triple carbon‐carbon bonds with CO2 represent an emerging research area in synthetic organic methodology. In particular, the combination of mild reaction conditions, stoichiometric acceptor/donorless conditions (visible light photoredox catalysis) and chiral catalysts contributed to a rapid development of this intriguing research area capable of creating chemical diversity/ complexity from readily available unsaturated hydrocarbons and CO2 as a C1‐buinding block. The most recent developments in the field have been collected in the present review article and organized, based on the different sets of π‐systems/intermediates/reactive partners employed ( i.e., nickelalactones, organo‐halides) as well as synthetic strategies ( i.e., visible‐light photo redox catalysis). Abstract :